Peoples (sub) Exposed: On the Importance of Remaining History - García Gómez, Patricia (Eikón / Imago, 2019)
It seems that we can talk about multiculturalism in a globalized world. However, the processes of homogenization of global capitalism force as to speak of loss, of impoverishment, of voices that are silenced, rather than of the coexistence of different cultures. Time and human experience has been emptied and standardized under the rhythms marked by the logic of capital. Time of capitalism emerges as a new form of barbarism that destroy people’s own times. We need to investigate new time models that allow us to talk about the plurality of stories –and histories–, and to promote new connection networks. For this reason, we study the proposal of Georges Didi-Huberman, who claims an epistemological renovation for art history, a new way of studying history and image that allows us to talk about other different times than those of power, other ways in which images, singular stories from different times and cultures, could be connected.